Cytokinins Induce Transcriptional Reprograming and Improve Arabidopsis Plant Performance under Drought and Salt Stress Conditions - Golan, Yelena; Shirron, Natali; Avni, Avishi; Shmoish, Michael; Gepstein, Shimon (Frontiers in Environmental Science, 2016)
In nature, annual plants respond to abiotic stresses by activating a specific genetic program leading to early flowering and accelerated senescence. Although, in nature, this phenomenon supports survival under unfavorable environmental conditions, it may have negative agro-economic impacts on crop productivity. Overcoming this genetic programing by cytokinins (CK) has recently been shown in transgenic plants that overproduce CK. These transgenic plants displayed a significant increase in plant productivity under drought stress conditions. We investigated the role of CK in reverting the transcriptional program that is activated under abiotic stress conditions and allowing sustainable plant growth. We employed 2 complementary approaches: Ectopic overexpression of CK, and applying exogenous CK to detached Arabidopsis leaves. Transgenic Arabidopsis plants transformed with the isopentyltransferase (IPT) gene under the regulation of the senescence associated receptor kinase (SARK) promoter displayed a significant drought resistance. A transcriptomic analysis using RNA sequencing was performed to explore the response mechanisms under elevated CK levels during salinity stress. This analysis showed that under such stress, CK triggered transcriptional reprograming that resulted in attenuated stress-dependent inhibition of vegetative growth and delayed premature plant senescence. Our data suggest that elevated CK levels led to stress tolerance by retaining the expression of genes associated with plant growth and metabolism whose expression typically decreases under stress conditions. In conclusion, we hypothesize that CK allows sustainable plant growth under unfavorable environmental conditions by activating gene expression related to growth processes and by preventing the expression of genes related to the activation of premature senescence.